Aplicação do instrumento de avaliação do jogador de futebol (IAJF) em jogos da Copa do Mundo - Rosa, Paulo Rogério da Silva Marques da [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Soccer is currently one of the most practiced sports in the world. The practice of this sport varies from leisure and play to high-performance sports. Soccer is a collective sport considered a social, economic and political phenomenon that attracts attention from investors, media and government officials seeking to promote spectacles, consuming products, mainly related to health, regardless of gender or age. Soccer is the sport that receives significant attention and encouragement from big investors. As in many countries, Brazil is no different because athletes of this modality are the best paid and have greater international visibility. Brazil, a country that reveals great talents, is considered a power in this sport. From Pelé to Garrinha, from Careca to Sócrates, from Ademir da Guia to Rivelino, and currently Neymar, there are several players who became references in terms of very skilled techniques. A highly skilled run of a player or a creative tactical performance of a soccer team charms fans and spectators but also catches the eye of researchers seeking to understand the determinants of performance at such a high level. The position in the field where the player acts greatly influences his performance. The variables of physical capacity (velocity, agility, power, strength, aerobic and anaerobic resistance), motor, cognitive, and morphological variables are characteristics that influence in some way the performance of athletes in the soccer game. Soccer consists of three main factors, namely: the tactical, the technical and the physical aspects. Meeting these factors is key to the outcome of the game. In the present study the technical aspect of the soccer was focused. Specifically, the present study assessed the technical skills of the professional soccer player by the Instrumento de Avaliação do Jogador de Futebol (IAJF), initially proposed by Gama (2003)

O futebol de campo é atualmente um dos esportes mais praticados no mundo. A prática desse esporte varia do lazer, da brincadeira ao alto rendimento esportivo. O futebol é um esporte coletivo considerado de fenômeno social, econômico e político que atrai atenção de investidores, da mídia e de governantes buscando promover espetáculos, produto buscando cultivar hábitos de vida ativa a todos, independente do gênero ou idade. O futebol é a modalidade que mais recebe atenção e incentivo de grandes investidores. Assim como em muitos países, no Brasil não é diferente pois os atletas desta modalidade são os mais bem pagos e que tem maior visibilidade internacional. Revelador de grandes talentos, o Brasil é considerado uma potência nesta modalidade. De Pelé a Garrinha, de Careca a Sócrates, de Ademir da Guia a Rivelino, e atualmente Neymar, encontramos referências de jogadores de futebol de campo de técnica diferenciada. Uma execução altamente habilidosa de um jogador ou um desempenho tático criativo de um time de futebol encanta fãs e espectadores, mas também chama a atenção de pesquisadores que buscam compreender os fatores determinantes de desempenhos de tão alto nível. A posição em campo onde o jogador atua influencia sobremaneira seu desempenho. As variáveis de capacidade física (velocidade, agilidade, potência, força, resistência aeróbia e anaeróbia), motora, cognitiva, morfológicas, são características que influenciam de algum modo o desempenho de atletas no jogo de futebol. Podemos considerar que o futebol de campo consiste de três fatores, a saber: o tático, o técnico e o físico. A reunião desses fatores é determinante para o resultado do jogo. No presente estudo foi focalizado o aspecto técnico ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Futebol - Avaliação; Jogadores de futebol; Capacidade motora; Copa do mundo (Futebol)